Strategi Peningkatan Target Wajib Pajak Bagi UMKM Dengan Metode Analytic Network Process (ANP) - Imelda Dian Rahmawati; Muhammad Nasih (Universitas Muhammadiyah Sidoarjo, 2020)
The development of MSME in Indonesia is very rapid, but this development is not supported by tax compliance. This requires a strategy that needs to be designed by DGT so that this potential can be optimized. The purpose of this study was to determine strategies for increasing tax revenues from the micro small and medium business sector (MSMEs) with the Network Process Analysis (ANP) method. This type of research is field study research. Data sources used in this study are primary and secondary data sources. Data collection techniques in this study used observation, interview, documentation, questionnaire, and literature study techniques. Data analysis techniques in this study used the ANP method. The results of this study, among others, based on the NetworkProcess Analysis (ANP) method, obtained priority strategies for increasing revenue from the MSME sector with the Network Process Analysis (ANP) method. The first rank that gets the highest value is the strategy to increase tax services to MSME taxpayers. Tax services to MSME taxpayers include ease in tax reporting, ease in tax payments, and ease in accessing tax information.